Kepemimpinan Yesus Sebagai Acuan Bagi Kepemimpinan Gereja Masa Kini - Yahya Wijaya (Sekolah Tinggi Theologia Jaffray, 2018)
This article compares the leadership model of Jesus with those of the formal prominent leaders in his time. Rooted in a deep spiritual relationship with his Father, and moved by a compassionate heart, Jesus’ leadership challenges today’s church leadership practices in Indonesia which is marked by either institutional centralization, absolute local autonomy, or traditionalism. Artikel ini membandingkan antara model kepemimpinan Yesus dengan model-model kepemimpinan para penguasa formal di zamannya. Berakar pada hubungan spiritual yang mendalam dengan Bapanya, dan digerakkan oleh hati yang berbelaskasihan, kepemimpinan Yesus menantang praktik-praktik kepemimpinan gereja di Indonesia masa kini yang ditandai oleh sentralisasi institusional, otonomi lokal yang absolut, atau tradisionalisme